A look at professional education: reasons and how to deal with dropouts at the Federal Institute of Acre, Campus Cruzeiro do Sul (Research, Society and Development, 2022)
School dropout is a multifaceted and multicausal phenomenon that may be associated with individual factors, internal factors, and factors external to the institution, and is a problem of the family, the school, and society. It is believed that by identifying the reasons for dropping out, it is possible to reflect and propose preventive actions, seeking to mitigate this problem. The aim of this study was to identify the reasons for dropouts at the Instituto Federal do Acre, Campus Cruzeiro do Sul, in technical courses integrated to high school, identifying the actions of the institution in face of this problem. The research is quali-quantitative, supported by literature and document review, and has as instrument of data collection the semi-structured questionnaire applied to servers of the Student Assistance Center. In the documents analyzed, about 214, we found a total of 63% of dropouts in the Agricultural course and 37% in the Environmental course. Factors such as location, change of city, indecision about the course and change of course were decisive for the student's departure from the institution. It can be concluded that the institution has been taking actions aimed at the permanence of the students, such as: financial aid, to minimize expenses with transportation and food; encouragement to participate in projects and events of teaching, research and extension; calls for monitoring. However, it is necessary to deepen the work regarding the dropout, acting preventively, knowing the reality of the student, tracing his socioeconomic profile, promoting moments with the community, publicizing the courses offered, intensifying teaching actions, improving the infrastructure and, above all, continue expanding permanence and success policies.